Meningkatkan Persaingan Bisnis Bunga Telang Melalui Digital Marketing - Sri Rahmayanti; Dheajeng Novida Naila Rochmatin; Melinda Dwi Safitri; Hamdan Syahrul Efendi; Mohammad Farraas Salsabiil (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Utilization of the internet in this era is very felt for users, one of which is in the field of business with digital marketing. Digital marketing has the ability to reach all levels of society wherever they are without being limited by geography or time. Until now, there have not been many butterfly flower businesses that have advanced because they are inferior to other types of businesses. The purpose of this study was to determine the use of digital marketing as the chosen means to increase competition in the telang flower business. The method used in this study is a qualitative method that will analyze and explain a phenomenon, event, occurrence, or behavior of a person or group of people towards something. Digital marketing if it can be used, it will have a tremendous impact on a business. MSME “Sang Telang” in increasing business competition uses digital marketing because it is the most relevant tool in increasing sales.